A single scalp nodule as the first presentation of acute lymphoblastic leukemia (KMT2A::MLLT3) in a healthy-appearing infant: a case report - Pellegrino, Francesco; Coppo, Paola; Barisone, Elena; Bertorello, Nicoletta; Spadea, Manuela; Fagioli, Franca (Frontiers in Pediatrics, 2023)
Background Infant leukemia is a rare form of acute leukemia diagnosed prior to the age of 1 and is characterized by an extremely poor prognosis due to its dismal response to current therapeutic approaches. It comprises about 4% of all childhood cases of acute lymphoblastic leukemia (ALL). Isolated initial cutaneous involvement in ALL is uncommon, and even more so in infant ALL. Case presentation Here, we present the case of a 2-month-old healthy-appearing infant, initially presenting with a single scalp nodule and subsequently diagnosed with an infant ALL. The leukemia was characterized by the most immature B-lineage immunophenotype [pro-B ALL/B-I, according to the European Group for the Immunological Characterization of Leukaemias (EGIL) classification] and chromosomal translocation t(9;11)(p22;q23), resulting in fusion gene KMTLA2::MLLT3, which is considered a negative prognostic factor. The patient underwent hematopoietic stem cell transplantation and is still in remission. Conclusions This case is peculiar because of the rare occurrence of isolated initial cutaneous involvement in ALL. Despite the healthy appearance of the patient, every suspicious symptom suggestive of malignancies should be further investigated to anticipate the diagnosis and start treatment early.